2003
DOI: 10.1038/sj.bjc.6600798
|View full text |Cite
|
Sign up to set email alerts
|

Association of perceived physician communication style with patient satisfaction, distress, cancer-related self-efficacy, and perceived control over the disease

Abstract: The aim of the study was to investigate the association of physician communication behaviours as perceived by the patient with patient reported satisfaction, distress, cancer-related self-efficacy, and perceived control over the disease in cancer patients. Questionnaires measuring distress, self-efficacy, and perceived control were completed prior to and after the consultation by 454 patients attending an oncology outpatient clinic. After the consultation, the patients also rated the physicians' communicative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
351
1
18

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(379 citation statements)
references
References 37 publications
9
351
1
18
Order By: Relevance
“…The importance of a trusting and confident doctor-patient relationship as a part of any clinical encounter is undeniable, and in this interplay the physician's communication behaviours as perceived by the patient are of paramount importance [8,10,11,29]. However, problems arise when doctors are also researchers [6,12,25].…”
Section: Discussionmentioning
confidence: 98%
“…The importance of a trusting and confident doctor-patient relationship as a part of any clinical encounter is undeniable, and in this interplay the physician's communication behaviours as perceived by the patient are of paramount importance [8,10,11,29]. However, problems arise when doctors are also researchers [6,12,25].…”
Section: Discussionmentioning
confidence: 98%
“…One study reported internal consistency for the total scale (α = .95) . The C I has been used with other oncology populations and shown good internal consistency (α's range between .84 and .88) (Heitzmann et al, 2011;Zachariae et al, 2003).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…For example, a survey of 454 patients attending an oncology outpatient clinic showed that physician attentiveness and empathy were associated with greater patient satisfaction, increased self-efficacy, and reduced emotional distress [12]. Street et al [13] found that patient participatory behaviours were associated with doctor supportive talk, further demonstrating the inter-relatedness of these behaviours.…”
Section: Introductionmentioning
confidence: 99%